Narratives Beyond the Classroom: Deploying Reflective Literacy and Mental Literacy to Foster Moral and Psychological Resilience - Chow Teng Poh; Ni Nyoman Parwati; Ketut Agustini; I Made Tegeh (KENDALI: Economics and Social Humanities, 2025)
This study explores an Exploration and Deployment (E&D) model that integrates reflective literacy and mental literacy to cultivate moral and psychological resilience in diverse educational and religious settings across Indonesia. Centered on the distribution of four bilingual books: Melampaui Kelas, Beyond the Classroom, Gema Keseimbangan, and Echoes of Equilibrium; the initiative reached over 40 institutions including schools, universities, religious organizations, and community libraries. These texts introduced adaptive-pervasive learning and the transformative role of mantra practices in fostering psychological well-being. In tandem, a 12-week mantra recitation program was deployed in selected institutions, guiding participants through daily practice, group reflection, and, where feasible, physiological monitoring (ECG). Pre- and post-program surveys assessed changes in emotional states, reflective capacity, and moral insight. Findings suggest that the integration of narrative-based literacy with spiritual practice significantly enhances participants’ self-regulation, empathy, and mental clarity. The study highlights the value of culturally rooted, community-embedded pedagogies in bridging educational innovation with spiritual tradition. This paper contributes to the discourse on moral education, adaptive learning, and community-based mental health strategies in the Global South.